Humble Dominion - Tubbs (Theology today, 1994)
“[I]f human dominion as despotic license is indefensible within the context of Old Testament theology, it is certainly unspeakable within the context of Jesus' teachings and New Testament christological models. Selfish dominance in any form is inconsistent with the model of obedient, humble service we find in Jesus Christ, the New Adam.”